2016
DOI: 10.1080/19490976.2016.1273998
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplant in severe and severe-complicatedClostridium difficile: A promising treatment approach

Abstract: Severe and severe-complicated Clostridium difficile infection (CDI) is associated with high morbidity and mortality. Colectomy is standard of care; however, post-surgical mortality rates approach 50%. Case reports suggest fecal microbiota transplant (FMT) is a promising treatment of severe and severe-complicated disease but there is a paucity of data. Here, we present a single center experience with a novel sequential FMT protocol for patients refractory to maximal medical therapy. This approach consists of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 59 publications
2
146
0
3
Order By: Relevance
“…New study directions on mineral metabolism and the intestinal microbiota should cover fields such as: the optimization of the minerals supplied in the diet of patients suffering from diseases for which microflora could be therapeutically applied; the effects of frequently overused mineral supplements on the intestinal microbiota; the impact of probiotics on the bioavailability of minerals and their metabolism; and the full identification of all human intestinal microbes undetectable by existing methods. Moreover, gut microbiota–host interactions serve as an essential target for development of new therapeutic strategies such as: fecal microbiota transplant (FMT) in the therapy of C. difficile infection, hepatic encephalopathy and gastrointestinal and behavioral symptoms of autism spectrum disorders; stool‐substitute therapies in the treatment of C. difficile infection; and the implementation of FMT, non‐traditional probiotics (e.g. F. prausnitzii and Clostridium butyricum ) and postbiotics (bacterial products and metabolic byproducts of probiotic organisms) in the therapy of inflammatory diseases .…”
Section: Resultsmentioning
confidence: 99%
“…New study directions on mineral metabolism and the intestinal microbiota should cover fields such as: the optimization of the minerals supplied in the diet of patients suffering from diseases for which microflora could be therapeutically applied; the effects of frequently overused mineral supplements on the intestinal microbiota; the impact of probiotics on the bioavailability of minerals and their metabolism; and the full identification of all human intestinal microbes undetectable by existing methods. Moreover, gut microbiota–host interactions serve as an essential target for development of new therapeutic strategies such as: fecal microbiota transplant (FMT) in the therapy of C. difficile infection, hepatic encephalopathy and gastrointestinal and behavioral symptoms of autism spectrum disorders; stool‐substitute therapies in the treatment of C. difficile infection; and the implementation of FMT, non‐traditional probiotics (e.g. F. prausnitzii and Clostridium butyricum ) and postbiotics (bacterial products and metabolic byproducts of probiotic organisms) in the therapy of inflammatory diseases .…”
Section: Resultsmentioning
confidence: 99%
“…Frozen FMT (donor‐selected or OpenBiome) was administered via colonoscopy or flexible sigmoidoscopy. If pseudomembranous colitis was identified during endoscopy, FMT was repeated every 3‐5 days until resolution of colitis per previously published protocol . Matching was performed by the statistical software based on age, sex, history of CDI in prior 60 days, antibiotic use and CDI severity.…”
Section: Methodsmentioning
confidence: 99%
“…However, the utility of FMT in severe or fulminant CDI, especially for critically ill, hospitalised patients, is not well described in the current literature. While there have been several publications demonstrating FMT to be safe and effective in this population, much of this data is uncontrolled and does not directly compare patients who received antibiotics plus FMT vs antibiotics alone (standard of care, SOC) . The aim of this study was to assess the outcomes of hospitalised patients with severe or fulminant CDI requiring intensive care who received antibiotics plus FMT compared to SOC.…”
Section: Introductionmentioning
confidence: 99%
“…Prior reports of FMT in critically ill patients occurred mostly in the context of CDI, where 1 in 10 patients with CDI requires care in an ICU or colectomy, or dies from CDI . The 2 largest cohort studies to date and the only RCT for severe CDI reported no serious adverse events attributable to FMT in a total of 91 patients with severe‐complicated CDI who received FMT . There does not appear to be an observed increase in risk for perforation attributable to colonoscopy‐delivered FMT.…”
Section: Discussionmentioning
confidence: 94%